The Role of UNODC in Combating Human Trafficking: A Case Study of Indonesian Migrant Worker Exploitation in Cambodia (2022) - Safira, Marsya; Padmi , Made Fitri Maya (Indonesian Scientific Publication, 2025)
Human trafficking remains a critical transnational challenge in Southeast Asia, with migrant workers in Indonesia facing heightened vulnerability to exploitation. This paper examines the role of the United Nations Office on Drugs and Crime UNODC in facilitating cooperation between Indonesia and Cambodia to counter such trafficking. The objective is to evaluate the effectiveness of UNODC’s initiatives as a multilateral facilitator in enhancing bilateral anti-trafficking efforts in the region,the study employs qualitative descriptive methods, drawing on 2022 UNODC reports, regional policy documents, and expert interviews to analyze institutional mechanisms, legal coordination, and operational support,findings indicate that UNODC has significantly contributed to law enforcement capacity-building, fostered diplomatic engagement, and promoted public awareness. Nevertheless, structural challenges—including inconsistent legal frameworks, limited cross-border coordination, and resource constraints continue to impede sustainable progress, Theoretically, the research contributes to understanding UNODC’s role in shaping multilateral governance structures against transnational crime. Practically, it provides policy recommendations to enhance cross-border cooperation and institutional resilience, the paper concludes that while UNODC plays an essential role in regional anti-trafficking efforts, long-term protection for migrant populations requires harmonized legal instruments, sustained education programs, and strengthened enforcement capacity. A more durable and collaborative framework is urgently needed to safeguard vulnerable groups across borders.